The effect of training on raising the efficiency of the school safety coordinator in public schools in Jeddah Governorate - Alzahrani, Abdullah Gormallah (Journal of Educational and Psychological Sciences, 2021)
The research aimed to identify the extent of the impact of training on the performance efficiency of the school safety coordinator in public schools in Jeddah governorate, highlighting the role of training in raising the efficiency of the school safety and security coordinator in public schools in Jeddah, and aimed at identifying the knowledge gained while participating in training on training efficiency, Identify the level of competence of the safety and security coordinator in public schools in Jeddah and from the point of view of the study sample. The researcher used the descriptive analytical method, as he used the questionnaire as a study tool. The study population consisted of (243) school safety coordinators and (380) school headmasters, students counselors, teachers and safety and security coordinators in public schools in Jeddah Governorate. Among the most important results of the study: the majority of the sample members strongly agree with the terms of the returner from training, the most important of which is to increase the safety coordinator's familiarity with their job duties, the majority of the sample members strongly agree with the phrases of knowledge that I gained during participation in training, among which the most important of which have developed my knowledge and information. The Safety and security Coordinator at public schools in Jeddah undertakes training of students and school staff on training on the evacuation plan which prepared in advance. Among the most important recommendations: Increase and intensify specialized training courses in the field of security and safety, establishing an electronic platform for safety training and courses throughout the year, linking training points of the safety coordinator with some incentives for job promotions.
Keywords: training; efficiency improvement; safety coordinator; public schools